Representing experiential knowledge: Who may translate whom?. Issue 1 (2nd January 2021) - Susam-Saraeva, Şebnem
ABSTRACT: This provocation piece discusses the difficulties of translating texts based on experiential and corporeal knowledge. Personal narratives often comprise such knowledge; therefore, their interpretation and rendering in other languages give rise to some controversial questions. For instance, do we need translators/interpreters with supposedly "analogous" life experiences to source authors/speakers? Who has "the right" to translate/interpret/represent whom? In this contribution, these questions are elaborated on by using the concepts 'secondary-witness' and 'debriefing', as well as examples from research on translation of childbirth narratives and recent debates in the film industry regarding representation.